Persistence and Recovery of Polystyrene and Polymethyl Methacrylate Microplastic Toxicity on Diatoms - Chongchong Meng; Huijie Yang; Yuan Du; Xiaokang Li (Toxics)
The increasing pollution of polystyrene (PS) and polymethyl methacrylate (PMMA) microplastics (MPs) has become a global marine environmental problem. Diatoms contribute nearly 40% of marine primary productivity and shape the nitrogen cycle in the oceans. However, the persistence of the phytotoxicity of MPs on diatoms, especially nitrogen assimilation, remains largely unknown. To examine the persistence of PS and PMMA toxicity in diatoms, two subexperiments (a 96 h exposure followed by a recovery phase) were conducted on Thalassiosira pseudonana at concentrations ranging from 0.001 to 1 mg/L. The results showed that PS and PMMA inhibited algal growth by 3.76–6.49% and 4.44–8.37%; increased oxidative stress by 10.06–30.51% and 30.46–38.12%; and caused ultrastructural damage by 14.24–25.56% and 12.28–20%, respectively, consistent with the downregulation of glyoxylate, dicarboxylate metabolism, and glutathione metabolism. At the recovery stage, the algal density induced by PS was significantly recoverable at 0.001 and 0.01 mg/L, consistent with the enhanced carbohydrate metabolisms. After recovery, the cell permeability and reactive oxygen species (ROS) levels induced by PS and PMMA were significantly decreased at 1 mg/L, respectively, which was closely related to the downregulation of glycine, serine, and threonine metabolism and the upregulation of pantothenate and coenzyme A biosynthesis. Moreover, the inhibition of nitrogen assimilation enzymic activities induced by PS and PMMA was significantly recovered at 1 mg/L despite the downregulation of nitrogen metabolism. This study highlights the phenomena and mechanisms of phytotoxicity and recovery, and provides new insights for comprehensive understanding and evaluation of environmental risks of MPs.